If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7r = 2(4r + -9) Reorder the terms: 7r = 2(-9 + 4r) 7r = (-9 * 2 + 4r * 2) 7r = (-18 + 8r) Solving 7r = -18 + 8r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-8r' to each side of the equation. 7r + -8r = -18 + 8r + -8r Combine like terms: 7r + -8r = -1r -1r = -18 + 8r + -8r Combine like terms: 8r + -8r = 0 -1r = -18 + 0 -1r = -18 Divide each side by '-1'. r = 18 Simplifying r = 18
| (9y/14)/(6/14) | | -7(x+1)+7(7+x)= | | 2x+(2x-8)=72 | | X-7/8=-7/12 | | X(-2x+5)=33 | | 6m-3=1/3m | | -15=(3n/5) | | X-7/8=7/12 | | 48x-4=13x+6 | | -7+6p=-97 | | X+x+(x-4)+(x-4)=72 | | -(2r+7s)+2(r+s)= | | 12/6*5 | | x-1.6=-2.5 | | -6(a-3)-7(5-4a)= | | 1/42/7 | | -9x-11y-8x+12y= | | 14-m/2=10 | | -5x-10=2-[x+4] | | 4-5a=4(1+8a) | | 4x^2^4-16x^4/12ux^5 | | 45/17 | | 7r+5=11 | | V=3812 | | X-6-20=142 | | 6b+16=4 | | 25*w*1=0 | | 6[3a+1]-30=3[2a-4] | | 15+2x=2x | | 5x+2(5x-15)=-60 | | I2/3z=9 | | 11-(9x)+2x-(-9)= |